PROMOTING THE SECOND-YEAR FAST TRACK STUDENTS’ AUTONOMY IN IMPROMPTU SPEAKING AT FELTE, VNU-ULIS - Phạm, Thị Lệ Tuyết (2021)
In the recent decades, the concept of learner autonomy has drawn attention from many researchers and educators. In attempt to explore the current situation of training learner autonomy in impromptu speaking for the second-year Fast Track students at Faculty of English Teacher Education, VNU-ULIS, this paper includes three parts in which theoretical background related two key terms “learner autonomy” and “impromptu speaking”, the research methodology as well as major findings and pedagogical implication basing on the data gathered will be fully clarified. To be more specific, the investigation involved the participation of 2 teachers and 39 students was pursued with three research instruments, classroom observations, questionnaires and interviews. The analysis of the collected data focused on student’s perceptions on learner autonomy in impromptu speaking, students’ and teachers’ strategies to foster self-learning and the effectiveness of techniques employed as perceived by both participants. In the process of data analysis, mismatches in teachers’ and students’ responses were mainly utilized to add into discussions. Afterwards, the issues raised in the discussions were explained in the light of theoretical framework to draw significant implication, which is expected to help better application of learner autonomy in impromptu speaking and also other skills in the future